2020
DOI: 10.1152/physrev.00042.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Spindles: Mechanisms and Functions

Abstract: Sleep spindles are burstlike signals in the electroencephalogram (EEG) of the sleeping mammalian brain and electrical surface correlates of neuronal oscillations in thalamus. As one of the most inheritable sleep EEG signatures, sleep spindles probably reflect the strength and malleability of thalamocortical circuits that underlie individual cognitive profiles. We review the characteristics, organization, regulation, and origins of sleep spindles and their implication in non-rapid-eye-movement sleep (NREMS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
577
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(607 citation statements)
references
References 645 publications
(1,014 reference statements)
30
577
0
Order By: Relevance
“…Spindles are involved in memory reactivation processes and are believed to function mechanistically by inducing plasticity in learning-related regions (Fogel and Smith, 2011;Fernandez and Luthi, 2019). The fact that spindles showed the largest association to weak item consolidation compared items with stronger encoding suggests that spindles are less effective in enhancing more strongly encoded information.…”
Section: Discussionmentioning
confidence: 99%
“…Spindles are involved in memory reactivation processes and are believed to function mechanistically by inducing plasticity in learning-related regions (Fogel and Smith, 2011;Fernandez and Luthi, 2019). The fact that spindles showed the largest association to weak item consolidation compared items with stronger encoding suggests that spindles are less effective in enhancing more strongly encoded information.…”
Section: Discussionmentioning
confidence: 99%
“…The Welch PSD determines the distribution of signal power over frequency [34], which reduces the estimated power spectra at the cost of reduced frequency resolution [35]. Human EEG studies have revealed that aging reduces the power of lower frequency bands, i.e., delta, theta, and sigma, while increasing that of the higher frequency bands, i.e., beta [36,37]. Moreover, it has also been noted that female human subjects have higher PSD than their male counterparts in the delta and theta range [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Human EEG studies have revealed that aging reduces the power of lower frequency bands, i.e., delta, theta, and sigma, while increasing that of the higher frequency bands, i.e., beta [36,37]. Moreover, it has also been noted that female human subjects have higher PSD than their male counterparts in the delta and theta range [36,37]. Similarly, in [38], Gabryelska et al validated that higher individual sleep quality is correlated with reduced NREM stage 2 (N2) sigma 2 spectral power in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and network properties leading to the emergence of spindles during NREM sleep are now well established (see Fernandez & Lüthi, 2020 for review). The pacemaker of this oscillation is the thalamus, a subcortical structure that is crucial for routing sensory information to the neocortex and for coordination of activity across different cortical areas.…”
mentioning
confidence: 99%
“…One promising line of research is that the spatiotemporal distribution of spindles during NREM sleep is a potential biomarker of various neuronal disorders (Fernandez & Lüthi, 2020), reflecting a disorganization in the underlying brain networks at the neuronal and circuit levels. It is possible that overnight sleep EEG will become a standard exam in yearly check‐ups, especially since cheap and high‐quality EEG recording systems are becoming available.…”
mentioning
confidence: 99%